Anomalous bathymetry and palaeobathymetric models of the Mozambique Basin and Riiser Larsen Sea - Castelino, Jude A.; Eagles, Graeme; Jokat, Wilfried (Earth and Planetary Science Letters, 2016)
In this study we introduce a palaeobathymetric model for the conjugate Mozambique Basin and Riiser-Larsen Sea built by employing backstripping techniques, compensating for dynamic topography and plate motions. The model is presented at 0.2◦×0.2◦grid resolution, making it suitable for future oceanographic and climate simulation model experiments aimed at a better understanding of the climatic and oceanographic relevance of oceanic gateways in the southern ocean. At the present day, the seafloor next to the Mozambican continental margin is around 300m shallower, and that in the central Mozambique Channel is almost 1300m shallower, than their conjugate areas or the predictions of oceanic thermal subsidence models. The cause of this anomalous depth is difficult to determine confidently because of sparse data, in particular concerning sediment thickness, and because of the wide range of amplitudes in modelled present-day dynamic topography. The distribution of shallow seafloor suggests that it might be attributed to the presence of thicker-than-usual oceanic crust, which in turn can be attributed to the Paleogene passage of the Quathlamba plume beneath the basin. We portray these effects in our palaeobathymetric models. In contrast, the Riiser-Larsen Sea has experienced fairly stable subsidence since its formation in Jurassic times, with only slight observable changes attributable to the onset of Antarctic glaciation and during the middle Miocene climate transition. Both basins display flexure over half-wavelengths of ∼60–80 km with amplitudes of 1500 m towards their continental margins. This plays an important role in models of palaeobathymetry for times older than 100 Ma. Near the margins, isolated areas of transitional or debatable crustal composition, including Beira High and Gunnerus Ridge, are depicted to subside in a similar fashion to oceanic crust. Further into the Indian Ocean, oceanic lithosphere younger than 100 Ma on both plates has subsided to depths that are typical of thermal subsidence models. ...